Meta-analysis on prognostic value of KRAS mutation in resected mass-forming cholangiocarcinoma. Issue 7 (July 2022) - Procopio, Fabio; Branciforte, Bruno; Nappo, Gennaro; Di Tommaso, Luca; Lleo, Ana; Torzilli, Guido
Abstract: Background: Despite survival improvements for other cancers, the prognosis of resected mass-forming cholangiocellular carcinoma (MFCCC) remains dismal. As a possible background of that, biologic factors could play some role. KRAS mutation has been investigated in the present systematic review and meta-analysis. Methods: MEDLINE, Embase and Cochrane Library databases were searched for studies reporting overall survival (OS) following liver resection for MFCCC with known KRAS status. Secondary outcomes included completeness of resection (R1 vs R0), pathological lymph node (LN) rate, tumor burden (multiple vs single), perineural invasion (PI) rate. Results: Eight studies comprising 604 patients resected for MFCCC were eligible for analysis. Of these, 23% of patients were mKRAS. The mKRAS MFCCC showed lower 1-year OS [odd ratio (OR) 3.45, 95% confidence interval (CIs) 1.85–6.42; p < 0.001], 3-years OS (OR 4.82, 95% CI 2.63–8.84; p < 0.001), and 5-years OS (OR 10.60, 95% CI 3.12–36.03; p < 0.001) compared to wtKRAS. Pooled-R1 resection rate was 18% for mKRAS and 23% for those with wtKRAS (OR 1.71, 95%CIs 0.70–4.19; p = 0.239). The pooled-pathological LNs rate was 23% in mKRAS vs 17% (OR 2.36, 95%CIs 0.75–7.48; p = 0.144). The pooled-multifocality rate was 55% in mKRAS vs 19% (OR 5.38, 95%CIs 1.76–16.48; p = 0.003), while the pooled-PI was 77% vs 31% (OR 6.59, 95%CIs 2.13–20.37; p = 0.001). Conclusion: The KRAS mutation is relatively frequent in MFCCC. The mKRAS is strongly associated with a shortened survival and higher tumoral aggressiveness. Testing for KRAS mutations could be a valuable adjunct in opening a scenario to new treatments and improving prognosis of patients with MFCCC.